Reconceptualizing biomedical paradigms for contraceptive care through feminist poststructuralism - Kerry Marshall; Lydia Wytenbroek; Victoria Bungay; John Oliffe (Witness)
In the specificities of contraceptive care, sexual health is comprehensively defined as overall physical, emotional, mental, and social well-being related to sexuality, including experiences that are safe, pleasurable, and free of coercion. However, due to the predominance of biomedical paradigms that promote and espouse ‘unbiased’ and ‘objective’ contraceptive care practices, comprehensive, inclusive, and safe sexual health care remains limited. In this article, we argue that feminist poststructuralist knowledge is needed to reconceptualize sexual health care, ultimately promoting reproductive justice through social change and advancement of reproductive rights. We demonstrate how nursing as a discipline and profession can utilize feminist poststructuralist theoretical perspectives to challenge dominant discourses within contraceptive care and lead to the delivery of equity-owed contraceptive and sexual health care for cisgender women and people who can get pregnant.